PENGARUH PENGEMBANGAN KARIR, BUDAYA ORGANISASI, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN BANK X (STUDI : KANTOR CABANG BANK X JAKARTA SELATAN) - Pryma Andhika Ramadhany; Erric Wijaya (Ibs Press, 2025)
This study analyzes the influence of career development, organizational culture, work motivation, and job satisfaction on the performance of permanent employees at Bank X South Jakarta Branch. The study employed a quantitative method with PLS-SEM approach and involved 100 respondents, with data analyzed using SmartPLS 4.0. The results indicate that career development and organizational culture have a significant effect on employee performance, while work motivation and job satisfaction show no significant effect. These findings highlight the importance of strengthening career development programs and fostering a positive organizational culture as the main strategies to improve performance. The implication for management is the need to design human resource policies that prioritize career development and organizational culture reinforcement to achieve optimal employee performance.